EVALUATING SOCIAL WORKERS WORKING LIFE QUALITY WORKING AT BUSHEHR UNIVERSITY OF MEDICAL SCIENCES IN 2015-16 - Niknam, Asad (International Journal of Clinical and Biomedical Research, 2016)
Background and Objective: Working life quality is a combination of working environment variables which could be effective on job satisfaction increase, personnel retention and finally qualitative and quantitative promotion of services in each organization. So, Ministry of Health is not exempt from this rule. The present study has been performed with the aim of determining social workers working life quality working in Bushehr province health centers. Methodology: This study has been conducted in cross- sectional method (descriptive - analytical) on 467 social workers of the province health center. Statistical population selection and participation is in census form. Data collecting tool is Walton two-part questionnaire. The first part of questionnaire includes social workers demographic information which includes 7 questions. The second part of questionnaire which contains social workers working life quality includes 35 questions. Regarding wide usage of this questionnaire, its reliability and validity is confirmed and it is in an acceptable level. The collected information was analyzed using SPSS version 20 software and the results were analyzed using descriptive - analytical statistics, Pierson correlation and unilateral variance analysis. Findings:The average total score of social workers working life quality 97.5 indicates desirable level. Considering all cases, also inclusion of confounding cases in regression model , in respect of demographic information only the variables of city (p=0.026) , age (p=0.006), working background( p=0.33) determine social workers working life quality. Conclusion: Working life quality of Boushehr province social workers is in desirable level and the impact of this variable is considerable in increasing job satisfaction rate and social workers motivation and as a result the society health level promotion. Regarding the role of some factors especially demographic factors in more promotion of this variable, necessity of identifying these factors and trying to improve working life quality has special significance.